PENGARUH PERMAINAN TRADISIONAL TERHADAP INTERAKSI SOSIAL PADA ANAK DI TPA AL-MUHTADIN - Mursyid, Muhamad; Badar, Faizah Muksin; Ganny, Fasya Al Fauziah; Amu, Aulia Ain Putri; Pontoh, Mutiara Sary; Aru, Siti Rahmiyaty (Elsia: Jurnal Psikologi Manusia, 2024)
This research examines the influence of traditional games on children's social interactions at Al-Mutakkin TPA. Traditional games, such as Domikado and Snakes and Ladders, are used as a means to strengthen children's social relationships. With an experimental research design and data collection methods through participant observation, this research involved children aged 6-12 years as subjects. The research results show that traditional games can improve children's social interaction skills, such as cooperation, communication and empathy. These findings underline the importance of preserving traditional games as an educational tool in supporting children's social development.